Use of the DD 136 strain of Neoaplectana carpocapsae Weiser (Rhabditida: steinernematidae) for control of corn earworm (Lepidoptera: noctuidae) - Bong, Joseph Choon Fah; Sikorowski, P. P. (Oxford University Press, 1983)

(untitled)
Field trials were conducted in the summer of 1981 to determine the effectiveness of the DD 136 strain of Neoaplectana carpocapsae Weiser in controlling, corn earworm, Heliothis zea(Boddie) larvae. The corn ears were artificially infested with H. zea larvae and subsequently sprayed with nematodes at 0, 4 × 103 and 4 × 104 nematodes/ml suspension. Eighty-eight percent control was obtained with 4 × 104 nematodes/ml in early June but less, 80% and 58% respectively, was observed in late June and early July. Thus, N. carpocapsae, survives better and is more effective in the early part of the season. All ears in the treated and control plots received some damage, but damage in all the treated plots was significantly lower than in the control.